2004
DOI: 10.1016/j.femsle.2004.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of transcriptional regulatory elements of glutamate-dependent acid-resistance systems of Shigella flexneri and Escherichia coli O157:H7

Abstract: The ability to withstand an acid-challenge of pH 2.5 or less by Shigella flexneri is a necessary trait for virulence and is generally believed to be restricted to the stationary-phase of growth. Earlier reports indicated the glutamate-dependent acid-resistance (GDAR) system of S. flexneri is under the regulation of rpoS, the gene encoding alternative sigma factor that is induced in the stationary-growth phase. The present study reports that unlike Escherichia coli O157:H7, S. flexneri cells when grown in minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Strain 52 is auxotrophic for thiamine, nicotinamide, and riboflavin (1). The strain had the same GDAR phenotype when grown in EG medium supplemented with vitamins or EG medium supplemented with yeast extract (5). Strain MG1655 is not an auxotroph, and the addition of yeast extract to EG medium had no influence on its GDAR phenotype.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Strain 52 is auxotrophic for thiamine, nicotinamide, and riboflavin (1). The strain had the same GDAR phenotype when grown in EG medium supplemented with vitamins or EG medium supplemented with yeast extract (5). Strain MG1655 is not an auxotroph, and the addition of yeast extract to EG medium had no influence on its GDAR phenotype.…”
Section: Methodsmentioning
confidence: 94%
“…However, the ability to survive exposure to acid is a complex phenotype, which depends on the growth phase, medium, and species of enteric bacteria (4,10,23). Two types of acid resistance pathways have been identified in the aerobically grown stationary-phase cells of E. coli and Shigella flexneri (5,23,51). The first acid resistance system is referred to as the glucose-repressible oxidative pathway and protects cells above pH 3.0 (23,24,38).…”
mentioning
confidence: 99%
“…When we performed RNA extraction on different Salmonella isolates we observed that previously tried and trusted RNA isolation protocols established in this laboratory [1,4,5] generated either poor 23S/16S ratios ( Table 1, sample 1) and/or poor 'Quality Scores' ( Table 1, samples 2 and 3) on both microfluidic platforms. Additionally, the quality score generated on BioAnalyzer platform was not consistent with the conventional indicator such as 23S/16S ratio (i.e., Table 1, sample 1 vs. sample 4) (Experion platform does not generate quality score for prokaryotic RNA samples).…”
Section: Resultsmentioning
confidence: 98%
“…RNA was isolated from stationary phase cells grown in LB broth for 18-20 h. Cells were stabilized with RNA stabilization reagent (RSR-3) [5] and RNA was isolated using Qiagen RNeasy kit as described before [1,5]. RNA was also isolated by suspending cells (after RNA stabilization) in hot Trizol reagent (65 o C) and purified using RNeasy silica columns and on-column DNase treatment (Qiagen).…”
Section: Rna Isolation Proceduresmentioning
confidence: 99%
“…However, in order to do so, S. flexneri must pass through the acid environment of the human stomach, which can be at pH,3 (Giannella et al, 1972). Additionally, enteric bacteria must survive low-pH stress external to the host, such as that encountered during passage through the environment, in acidic foods and in fermenting acidified faecal material (Bhagwat & Bhagwat, 2004;Lin et al, 1995). The ability of S. flexneri to survive these low pH levels appears to be an important pathogenic characteristic, and may be a contributing factor to the low infectious dose of 10-100 organisms required for shigellosis to occur (Gorden & Small, 1993).…”
Section: Introductionmentioning
confidence: 99%